Learning landscape assessing the educational value of the UP College of Architecture Complex landscape environment - Edralin-Servino, Grace C. (College of Architecture, University of the Philippines Diliman, 2010)
The physical space of a school oftentimes lacks the connection to the learning process that the school is programmed for. The landscape has valuable but underutilized resources, which can be developed as significant tools for learning. (potential for learning landscape) It is but proper that a school must have a safe, constructive, interactive and dynamic environment (learning landscape design) where students, professors and researchers are encouraged to apply theories, to validate design ideas and techniques in solving site problems and issues (learning landscape approach). The aim of this research is to highlight the current use and potential of the school landscape as a valuable knowledge resource (objective of learning landscape). Through participatory research and documentation, survey on related literature and case study, the researcher discusses how the Landscape Architecture Program of the University of the Philippines Diliman uses its landscape resources as tools for teaching, learning, and research (developing a methodology). With the documented laboratory activities and other strategies, the extent of educational use of its landscape is determined (measuring educational value). On how this can be fully implemented necessitates a framework or program guide for the school to design and manage its resources as a learning landscape and a functional laboratory (framework for establishing the learning landscape).